Assessment of the impact of the lesson study approach and didactic suitability criteria on mathematics teacher training from the onto-semiotic approach - Morales-Maure, Luisa; Vazquez, Evelyn García; Marimón, Orlando García; Ponce, Berenice Alfaro (Edelweiss Applied Science and Technology, 2025)
Improving mathematics teacher training requires evidence-based methodologies to enhance instructional quality and professional competencies. This study evaluates the impact of the EDEM Diploma Program, which integrates the Lesson Study approach and Didactic Suitability Criteria (DSC) within the Didactic-Mathematical Knowledge and Competencies Model (DMKC). The research follows a mixed-methods design, combining quantitative pre-test and post-test assessments with qualitative analysis of lesson planning and teaching reflections. The program was implemented in two phases: planning and execution of lesson study cycles, including collaborative lesson design, classroom implementation, reflective teaching discussions, and pedagogical assessment. Results indicate a 17.4 percentage point improvement in teachers' mathematical knowledge, with 82% demonstrating improved lesson structuring, 76% enhancing formative assessment strategies, and 88% gaining confidence in interactive teaching techniques. Findings highlight the strong correlation between teacher reflection and pedagogical improvement, emphasizing the effectiveness of structured, research-based professional learning. The study concludes that integrating Lesson Study and DSC enhances both mathematical knowledge and instructional quality, providing a scalable model for mathematics teacher training. Practical implications suggest the need for sustained professional development programs and longitudinal studies on teacher retention and student performance outcomes to assess the long-term impact of this approach.